Age- and Gender-Specific Components of the Metabolic Syndrome in 2228 First Graders: The PEP Family Heart Study. (17th February 2013) - Schwandt, Peter; Bertsch, Thomas; Liepold, Evelyn; Haas, Gerda-Maria
Abstract : Because first graders are critical for excess weight gain, we assessed components of the metabolic syndrome (MetS) using the pediatric definition of the International Diabetes Federation (IDF). We compared four MetS components as defined by the IDF with age- and gender-specific components in 2228 first graders at the age of 6. The growth curves were derived from 22113 children and adolescents who participated in the PEP Family Heart Study. The aim was to determine in first graders precise values of waist circumference (WC), blood pressure (BP), triglycerides (TG), and HDL-Cholesterol (HDL-C) based on growth curves that were developed for a large German population of youths and to assess the prevalence in terms of both definitions at this critical age. The prevalence of high blood pressure for age was 13% compared with only 2% according to IDF. Because of this considerable divergence, we propose to define MetS components based on national growth curves.